2023
DOI: 10.1371/journal.pone.0284465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relative weight limit set as a body weight percentage on work-related low back pain among workers

Abstract: Introduction A quarter of work-related low back pain (LBP) cases result from handling heavy loads in Japan. The maximum weight male/female workers can handle is 40%/24% of their body weight but has set a constant load weight in ISO 11228–1 and NIOSH lifting equation. The preventive effect of the relative weight limit on LBP has not been clarified. This study aimed to identify the effect of relative weight limits set as body weight percentages on LBP prevalence. Methods Data from 21924 workers were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Severe LBP prevalence ranged from 12% to 22% among no-handling workers and the rolling task workers handling ≤20 kg and 20-40 kg, whereas this was significantly higher at 53% among the rolling task workers handling >40 kg. In analyses using the same dataset as this study, 39% of lifting, lowering, and carrying task workers 10 and 39% of pushing and pulling task workers 11 complained of severe LBP. Moreover, Fujii and Matsudaira 15 reported that 38% of Japanese workers, housewives, and unemployed persons aged 20-79 years experienced severe LBP that interfered with work and life.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Severe LBP prevalence ranged from 12% to 22% among no-handling workers and the rolling task workers handling ≤20 kg and 20-40 kg, whereas this was significantly higher at 53% among the rolling task workers handling >40 kg. In analyses using the same dataset as this study, 39% of lifting, lowering, and carrying task workers 10 and 39% of pushing and pulling task workers 11 complained of severe LBP. Moreover, Fujii and Matsudaira 15 reported that 38% of Japanese workers, housewives, and unemployed persons aged 20-79 years experienced severe LBP that interfered with work and life.…”
Section: Discussionmentioning
confidence: 89%
“…These questionnaire items were similar to those used in our previous studies. 10 , 11 Data were extracted from the questionnaire for rolling and no-handling loads. For questioning on manual handling conditions, regularly managed load weights, and the severity of LBP, the initiation of the first LBP episode experienced by a worker in their current job was considered as the reference point for inquiry.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have established that dysfunction in any component of the IVD leads to intervertebral disc degeneration (IVDD), with NP tissue degeneration recognized as the primary cause ( Lama et al, 2022 ). IVDD is a multifactorial process with aging being a significant risk factor ( Ngo et al, 2017 ; Iwakiri et al, 2023 ; Novais et al, 2024 ). However, disc degeneration can also manifest independently of the aging process, making it challenging to distinguish between physiological disc aging and degeneration ( Soufi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have established that dysfunction in any component of the IVD leads to intervertebral disc degeneration (IVDD), with NP tissue degeneration recognized as the primary cause (Lama et al, 2022). IVDD is a multifactorial process with aging being a significant risk factor (Ngo et al, 2017;Iwakiri et al, 2023;Novais et al, 2024). However, disc degeneration can also manifest independently of the aging process, making it challenging to distinguish between physiological disc aging and degeneration (Soufi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%